Peningkatan Kompetensi Masyarakat dalam Mempromosikan Ekowisata melalui Pelatihan Internet Based Ecotourism Desa Pusung Kapal - Rima Meilita Sari; Tengku Muhammad Sahudra; Faiz Urfan; Ridhwan Ridhwan (Jurnal Pemberdayaan Masyarakat, 2024)
Pusung Kapal Village is one of the villages located in the coastal area of Seruway District, Aceh Tamiang Regency, Aceh Province. This village has tourism potential that can be developed as ecotourism including Pusung Siung Beach, Teluk Tamiang Beach, and Tuntong Laut Conservation. The potential that attracts visits is sea turtles (Batagur Borneoensis) and mangroves. However, this ecotourism potential is not yet known by many tourists due to the lack of information. This is due to the lack of knowledge and skills of the Pusung Kapal Village Pokdarwis to promote ecotourism. The method of implementing community service includes training and technical guidance related to ecotourism promotion through website-based internet utilization. The training provided knowledge and technical implementation of tourism promotion such as containing interesting content, presenting information on accessibility and tourist facilities, and promoting souvenirs and village products. After the training, Pokdarwisa members, villagers, and village officials produced content that they would later upload on the ecotourism website. Participants gained knowledge and skills of promotional content through utilizing cyberspace. Another advantage is that for the community it can be a source of increased income through increased tourist visits.